2019
DOI: 10.1039/c9ra03713f
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of antifungal dual-target (SE, CYP51) pharmacophore models and the discovery of novel antifungal inhibitors

Abstract: Fungal infections and drug-resistance are rapidly increasing with the deterioration of the external environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…According to the 2D diagram generated by the Maestro program ( Figure 7 ), it is notable that, in addition to the possibility of an interaction of the hydrogen bond type with residue Ile–423, monomethylsulochrin would also be able to establish a long chain of hydrophobic interactions with the active site of the protein. Studies reported in the literature, with the structure of CYP51, revealed that the hydrophobic interactions that its catalytic crack is capable of performing can be considered the main driving force for the binding of ligands ( Dong et al., 2019 ; Shi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2D diagram generated by the Maestro program ( Figure 7 ), it is notable that, in addition to the possibility of an interaction of the hydrogen bond type with residue Ile–423, monomethylsulochrin would also be able to establish a long chain of hydrophobic interactions with the active site of the protein. Studies reported in the literature, with the structure of CYP51, revealed that the hydrophobic interactions that its catalytic crack is capable of performing can be considered the main driving force for the binding of ligands ( Dong et al., 2019 ; Shi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the 3D interaction diagram ( Figure 8 ), it is possible to observe that the structure of monomethylsulochrin is easily allocated to the active site of CYP51, favoring the enzyme-substrate interaction to be less sensitive to the solvent of the biological medium ( Dong et al., 2019 ). This fact suggests that the parameters of the docking calculation performed here were correctly selected, aiming at good results and a lower computational cost.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking has shown great advancement in the predictions of therapeutic interventions by predicting bound conformations and free energies of binding for small-molecule ligands to macromolecular targets (protein) (El-Hachem et al, 2017). It is used in the evaluation of the binding mode of inhibitors and receptors to guide the optimization of lead compounds (Dong et al, 2019). The rule of thumb is "the higher the binding affinity, the lower the inhibition constant", and vice-versa (Ferreira et al, 2015).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…15 1, 3, 4-Oxadiazole block the 14α-demethylation of lanosterol into ergosterol, which is a major component of fungal cytoplasmic membranes and a bioregulator of membrane asymmetry, fluidity and integrity. [16][17][18][19][20][21][22][23][24][25] https://doi.org/10.18231/j.ctppc.2022.015 2582-5062/© 2022 Innovative Publication, All rights reserved.…”
Section: Introductionmentioning
confidence: 99%